Asuransi di bidang pariwisata sebagai suatu bentuk perlindungan wisatawan di Propinsi Bali = Tourism Insurance as a Form of Tourist Protection in The Province of Bali - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
This research of tourism insurance as a form of tourist protection is a research on normative law. The purpose of this research is to understand the legal construction of insurance that is covered in practice concerning the risks faced in tourism. Primary and secondary data in this research was gathered through library and field research by means of document review, questionnaires and guided interviews. The results of the research indicate that, in general, tourism insurance is arranged by service providers (hotel enterpreneurs, tour's and travel bureaus and managers of tourist objects), because of their legal liability. Therefore, tourism insurance is a kind of liability insurance, and in the case of incidental events which happen in the areas of tourist objects is a kind of insurance for the interest of a third party. Interests which are insured include life, personal misfortune, health, loss, and possessions destroyed as a result of fire and liability. In addition, the research shows that the determination of indemnity that must be paid by the insurer is not based on the financial loss that actually occurred, but it is determined at the initial establishment of the insurance agreement. Tourism insurance can be classified as a sum insurance (Sommen Verzekering), because the indemnity which is received by the concerned party cannot be said to have the same value as the loss that was actually suffered.